قرآنی سیرت نگاری کے اصول: تجزیاتی مطالعہ: The Foundations of Qur’anic Sīrah Writing: An Analytical Study - Aslam, Asifa; Shams-ur-Rehman, Prof. Dr. Ghulam (Al-Irfan, 2022)
The early Sīrah-writings had been recorded in the history chronicle and hadith literature but gradually it developed as an independent discipline to illustrate the various aspects of the life of the Holy Prophet Muhammad (peace be upon) him. However, an idiosyncratic shift has been observed in the writing and interpretation of the Sīrah during the last two centuries where the events of Sīrah were studied and interpreted under various trends by applying multiple methods to respond to the present challenges posed by the Orientalist or under the internal criticism on non-authentic reports recorded in historical sources. Thus, a valuable plethora of Sīrah literature has been compiled. A desire to record an authentic biography led the Sīrah-writers to present all aspects of the prophetic life as recorded in the Qur’an or at least according to the Qur’anic injunctions. Thus, the trend of Qur’anic Sīrah-writing emerged, and prominent scholars attempted to illustrate the life of the Holy Prophet as depicted in the Qur’an without explicitly devising the foundations and methodology of this discipline. The present study aims to explore the foundations of the Qur’anic Sīrah-Writing through carefully reading the literature produced by the eminent scholars of the field.